The Port Sector in Malaysia – Does Gender Diversity Exist at the Management Level? - Sharifah Halimah Syed Ahmad; Geetha Subramaniam; Shahrin Nasir (International Journal of Supply Chain Management, 2019)
Gender diversity has been a growing concern of the Government of Malaysia particularly the low representation of women in the decision-making level. Diversity in leadership and openness to new perspectives is crucial for charting the course in business.  Companies that are diverse in its board are stronger, better positioned to tackle external and internal challenges and more focused on the bottom line. In Malaysia, in 2016, women represent only 17.9% at the decision-making level of the top 50 Public listed companies.  Women participation in the managerial positions has largely stagnated over the year. The figure of 17.9% is low compared to more developed countries such as Australia (36%) and the Philippines (48%) within the Asian region.  Malaysia is essentially a maritime country; about 90% of the international trade are transacted through the port.  Hence, the purpose of this study is aimed at determining whether gender diversity exist at management level and examining the perceptions of the management level towards women involvement in port management.   10 questionnaires on profiling of major port operators in Malaysia have been distributed.   90% responded.  The study results show that that level of women participation at the board of directors and the management level is relatively low. There is a relationship between level of women participation and the lack of agenda on gender diversity in the organisation.  The study is important as the nation target to be a high-income nation by 2020, the talent repository need to be taken in greater importance.